Symptomatic eating epilepsy: two novel pediatric patients and review of literature - Fabiana Vercellino; Laura Siri; Giacomo Brisca; Marcello Scala; Antonella Riva; Mariasavina Severino; Pasquale Striano (BMC, 2021)
Abstract Eating epilepsy (EE) is a form of reflex epilepsy in which seizures are triggered by eating. It is a rare condition but a high prevalence has been reported in Sri Lanka. In EE, the ictal semiology includes focal seizures with or without secondary generalization or generalized seizures. Some cases are idiopathic while focal structural changes on imaging, if present, are often confined to the temporal lobe or perisylvian region. On the other hand, some cases support the hypothesis of a genetic aetiology. The prognosis of EE is extremely variable due to the different nature of the underlying disorder. We describe two patients with symptomatic eating epilepsy, a 13-year-old boy with a bilateral perisylvian polymicrogyria and a 2-year-old boy with a genetic cause. The presence of structural lesions or the dysfunction of specific cortical regions in the context of a germline genetic alteration might lead to a hyperexcitation fostering the epileptogenesis. We review the available literature to clarify the aetiopathogenesis and the mechanisms underlying EE to improve the diagnosis and the management of these rare conditions.